Moldova Financial Sector Assessment Program : Stress Testing - International Monetary Fund (Washington, DC, 2015)
This note discusses the stress tests that were carried out on Moldova’s banking system as part of the 2014 financial sector assessment program (FSAP) update. The objective of this exercise was to assess the resilience of the banking system to major sources of risk. The stress tests were conducted in collaboration with the National Bank of Moldova (NBM), and complement other approaches, such as the analysis of financial indicators and the assessment of the quality of supervision. The stress tests focused on the banking system and covered all 14 banks operating in the country. Four macroeconomic scenarios were considered in the financial stability assessment. The stress tests include a comprehensive assessment of risk factors. Potential credit risk losses on the loan book represent the most important risk factor for the banking system. The stress tests also assessed the liquidity in foreign currency, and yielded similar results. However, there are a couple of banks whose ability to meet the liquidity norms is based on relatively large-scale cross-border interbank placements, and there are some doubts about the genuine liquidity of these positions. This note is structured as follows: section one gives executive summary; section two presents a brief description of the banking sector in Moldova and stress test coverage; section three describes the macroeconomic scenarios used in the stress tests; section four details the different methodologies used in the solvency stress tests; section five describes the liquidity stress tests; and section six concludes.